CRITICAL SUCCESS FACTORS FOR KNOWLEDGE TRANSFER: A CASE STUDY OF AUSTRALIAN GOVERNMENT WEBSITE - Nurdiana A.; Ross Smith; Vanessa Cooper; Noraizah A.B (INTERNATIONAL JOURNAL OF LAW, GOVERNMENT AND COMMUNICATION (IJLGC), 2023)
This paper presents and discusses the indicators for critical success factors (CSFs) for knowledge transfer (KT) via an Australian government website. The indicators are based from knowledge management (KM), customer service (CS) and web-based self-service (WSS) literature. The research explores CSFs from a case study at Department of Education in Australia that is known as AUSED from the perspective of provider. This study employed interpretive case study with qualitative methods. Primary data derived from interviews with nine government officers that are involved in the development and management of government website. Qualitative content analysis by inductive approach was used as analysis technique. From the analysis, 11 CSFs were identified. These CSFs were then being grouped into six themes, namely management role, user focus, employee focus, content focus, technology focus and organisational culture. Then these CSFs were being validated in a focus group to finalise the CSFs for knowledge transfer via Australian government website. This study used a single study of one government agency in Australia. Therefore, the result may not be applicable to other government departments due to differences of business areas. Nevertheless, this study produces a list of CSFs for strategic management in government agency to consider for development and management of government website. The list might lead towards a best guideline for knowledge transfer to happen via government website.